An adaptable metric shapes perceptual space - Hisakata, Rumi; Nishida, Shin'ya; Johnston, Alan (Elsevier (Cell Press), 2016)
How do we derive a sense of the separation of points in the world within a space-variant visual system? Visual directions are thought to be coded directly by a process referred to as local sign, in which a neuron acts as a labeled line for the perceived direction associated with its activation. The separations of visual directions are however not given. Nor are they directly related to the separations of signals on the receptive surface or in the brain which are modified by retinal and cortical magnification, respectively. To represent the separation of directions veridically the corresponding neural signals need to be scaled in some way. We considered this scaling process may be influenced by adaptation. Here we describe a novel adaptation paradigm, which can alter both apparent spatial separation and size. We measured the perceived separation of two dots and the size of geometric figures after adaptation to random dot patterns. We show that adapting to high density texture not only increases the apparent sparseness (average element separation) of a lower density pattern, as expected, but paradoxically, it reduces the apparent separation of dot pairs and induces apparent shrinkage of geometric form. This demonstrates for the first time a contrary linkage between perceived density and perceived extent. Separation and size appear to be expressed relative to a variable spatial metric whose properties, while not directly observable, are revealed by reductions in both apparent size and texture density.